Komunikasi Model Lasswell dan Stimulus-Organism-Respose dalam Mewujudkan Pembelajaran Menyenangkan Kelas 3 SD - Aisyah Faradhilah Yasmin; Arif Bagus Priyanata (STKIP AL HIKMAH SURABAYA, 2024)
This research was conducted on the basis of problems in educational communication. The research subjects were 3rd grade elementary school students. The object of this research is the ability to communicate in creating fun learning by using the Lasswell and stimulus-organism-response (SOR) communication models. This study aims to determine the pattern of communication that is applied to grade 3 SD. The method used in this research is qualitative. The results of this study indicate that communication has an important role for the advancement of education. Communication that has been designed systematically so that students participate in the learning process in a fun way and influence the cognitive and affective aspects of the learning process is achieved.